1988
DOI: 10.1128/jb.170.6.2855-2857.1988
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation of constitutive mutants for L-arabinose utilization in Bacillus subtilis

Abstract: Constitutive mutants for L-arabinose utilization were isolated from Bacillus subtilis 168T+ and showed resistance to D-fucose, a nonmetabolizable analog of L-arabinose. The mutations that conferred the constitutive phenotype (Arac) were mapped between cysB and hisA. All the mutants showed an isomerase activity which was reduced to 50 to 70% in the presence of L-arabinose and to 10% in the presence of glucose.The L-arabinose pathway in Bacillus subtilis has been described; its enzymes are inducible, and the iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…In a previous work a collection of B. subtilis strains carrying mutations that mapped on the araR region was characterized (33,44). Chromosomal DNA from these strains was amplified by PCR, using oligonucleotides ARA13 and ARA18, and sequenced.…”
Section: Vol 188 2006 Characterization Of the B Subtilis Regulatormentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous work a collection of B. subtilis strains carrying mutations that mapped on the araR region was characterized (33,44). Chromosomal DNA from these strains was amplified by PCR, using oligonucleotides ARA13 and ARA18, and sequenced.…”
Section: Vol 188 2006 Characterization Of the B Subtilis Regulatormentioning
confidence: 99%
“…In previous studies, B. subtilis mutants constitutive for arabinose utilization and mutants showing growth deficiencies in minimal medium with arabinose as the sole carbon source were isolated after mutagenesis with NЈ-methyl-NЈ-nitro-N-nitrosoguanidine and mapped in the araR locus (33,44). This region of the chromosome was sequenced, and three novel single missense mutations conferring an AraR s phenotype (E-1423K, G-2153V, and G-2153D) and one responsible for a constitutive phenotype AraR Ϫ (G-1383E) were detected.…”
Section: Mutagenesis Of the Arar Allele And Isolation Of Arar Defectimentioning
confidence: 99%
“…Transcriptional studies demonstrated that the expression of the araABDLMNPQabfA operon is directed by a strong A -like promoter identified upstream from the translation start site of the araA gene and that expression from the araABDLMNPQ-abfA promoter is induced by L-arabinose and repressed by glucose (24). The araR locus defined by three additional classes of mutations affecting L-arabinose utilization (17,18,25), at about 294°on the B. subtilis genetic map, was recently cloned (23). This region comprises two open reading frames with divergently arranged promoters, the regulatory gene, araR, and a partially cloned gene, termed araE.…”
Section: Insertional Inactivation Of the Arae Gene Leads To A Conditimentioning
confidence: 99%
“…Three additional classes of mutations affecting L-arabinose utilization were identified: (i) mutations conferring an Ara Ϫ phenotype to strains bearing the araA, araB, and araD wildtype alleles (39,40), (ii) mutations leading to constitutive expression of the three genes (47), and (iii) mutations conferring a conditional Ara Ϫ phenotype which was dependent on the concentration of sugar (39,40). These mutations were mapped at about 294Њ on the B. subtilis genetic map and define another ara locus.…”
mentioning
confidence: 99%